WRMP and associated risk factor among rubber tapper a community based study at Kg Pong, Pengkalan Hulu, Perak - Sudaratt, Pet Tong (2016)
Rubber tapping activities exposes workers too many risk factor for work related musculoskeletal problems (WRMP). Rubber tapping involves repetitive and high paced work, static muscle loading, non-neutral body postures, forceful physical exertion, and all potential risk factor for development of WRMP. In this study, a cross sectional study was carried out 1) to determine the prevalence of WRMP among rubber tapper, 2) to determine the psychosocial factors that can contribute to WRMP, 3) to assess postural problem, 4) to identify whether there is a mismatched between rubber tapper tools and rubber tapper hand and 5) to identify the relationship between psychosocial factors and physical factors among rubber tapper. Data collection was done using four instruments, namely Nordic Musculoskeletal Questionnaire (NMQ), Job Content Questionnaire (JCQ), Rapid Upper Limb Assessment Tools (RULA) and Anthropometry Measurement. Questionnaire were administered to (n=70) rubber tappers to measure WRMP and psychosocial factors using NMQ and JCQ. Ergonomic risk exposure levels were measured for the tappers using RULA. Mismatch between rubber tappers hand and tools were measure using anthropometry measurement. Based on the results obtained, 64.3% of the rubber tappers suffer from lower back pain. The study also found that MSCs and psychosocial factors are significant. In conclusions, WRMP among rubber tappers are well known and can be prevented or controlled by the education programs, training and administrative short working time. Tools used by rubber tappers also can be improved.